Off-label Medications Use in the Eastern Province of Saudi Arabia: The Views of General Practitioners, Pediatricians, and Other Specialists. (February 2020) - AbuAlsaud, Zainab; Alshayban, Dhfer; Joseph, Royes; Pottoo, Faheem Hyder; Lucca, Jisha Myalil
Background: Off-label drug prescribing remains a major pediatric health concern worldwide. The lack of studies in this vulnerable population causes many practitioners to prescribe drugs outside their license. This study aims to investigate and compare the current knowledge and views of general practitioners, pediatricians, and other specialists toward off-label pediatric prescribing.Methods: A descriptive, cross-sectional–based study conducted on a random sample of physicians who work in three different hospitals in the Eastern Province of Saudi Arabia.Results: Data were obtained from three hospitals, comprising a total of 160 practitioners. Overall, more than half of the participated practitioners (54%) were familiar with the definition of off-label prescribing. Thirty percentage of participated practitioners agreed that more than 10% of their prescribed medicines to children were off-labeled. A majority of participants expressed concerns over the efficacy (83%) and safety (92%) of off-label prescribing to children. Importantly, a noticeable proportion of the responders claimed that they sometimes observed an adverse drug reaction (n = 23; 20%) or treatment failure (n = 43; 37%) following off-label prescribing medicines to children. Only 46% participants have always informed the parents or guardian about the off-label prescription of medications to their children.Conclusion: A Large number of physicians are familiar with the concept of off-label prescribing of medicines to children in the Eastern Province of Saudi Arabia. Safety and efficacy are the main concerns of prescribing such medications. Policies toward improving pediatric clinical research and supporting the safety and efficacy of the drugs should be encouraged.